CottonMD: a multi-omics database for cotton biological study. Issue Volume 51:Issue D1(2023) (10th October 2022) - Yang, Zhiquan; Wang, Jing; Huang, Yiming; Wang, Shengbo; Wei, Lulu; Liu, Dongxu; Weng, Yonglin; Xiang, Jinhai; Zhu, Qiang; Yang, Zhaoen; Nie, Xinhui; Yu, Yu; et al.
Abstract: Cotton is an important economic crop, and many loci for important traits have been identified, but it remains challenging and time-consuming to identify candidate or causal genes/variants and clarify their roles in phenotype formation and regulation. Here, we first collected and integrated the multi-omics datasets including 25 genomes, transcriptomes in 76 tissue samples, epigenome data of five species and metabolome data of 768 metabolites from four tissues, and genetic variation, trait and transcriptome datasets from 4180 cotton accessions. Then, a cotton multi-omics database (CottonMD, http://yanglab.hzau.edu.cn/CottonMD/ ) was constructed. In CottonMD, multiple statistical methods were applied to identify the associations between variations and phenotypes, and many easy-to-use analysis tools were provided to help researchers quickly acquire the related omics information and perform multi-omics data analysis. Two case studies demonstrated the power of CottonMD for identifying and analyzing the candidate genes, as well as the great potential of integrating multi-omics data for cotton genetic breeding and functional genomics research.